Activity research of institutional investors in the context of financial marketing - Новошинська, Любов Василівна (Technology audit and production reserves, 2015)
The market situation in the financial market of Ukraine and the euro-zone is investigated. The appearance and transformation of financial globalization, financialization, institutionalization of the financial market are analyzed. The true and apologetics of consumer behavior of customers are determined. The main prerequisites for the use of financial instruments are identified in order to establish the marketing prospects for its use in the activities of institutional investors - Collective Investment Institutions (CII), insurance companies, private pension funds. The investigations show that these investors occupy a rather narrow segment as investment transformers in gross domestic product. The usefulness and importance of obtained data consist in the fact that the philosophy of financial marketing promotes the use of strategic marketing as a paradigm (theoretical model) revitalization of institutional investors. It is investigated the theoretical principles of formation and development of the financial marketing activities of non-bank institutional investors.